Effects of Addition of Vitamin C on Artificial Feed for the Growth of Humpback Grouper’s Seeds - Rahman Tamutu; Syamsuddin Syamsuddin; Mulis Mulis (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2018)
This study aims to determine the effect of adding different doses of vitamin C to otohime artificial feed for the growth of humpback grouper (Chromileptis altivelis) seeds. This study used an experimental method and a completely randomized design (CRD) with 4 treatments and 3 replications. The results showed that the highest growth in length and weight was shown in treatment D respectively 1.96 cm and 4.14 g, followed by treatment C amounting to 1.87 cm and 4.12 g, followed by treatment B 1.65 cm and 4 , 07, and the lowest in treatment A of 1.57 cm and 3.97 g. The results of the analysis of variability in humpback grouper seed weight showed that the addition of vitamin C, which had a different significant effect (p